The Analysis of Broujerd city’s Sustainability Compared with Iran Urban Centers (تحقیقات کاربردی علوم جغرافیایی)
Rapid urban development in social, economical, cultural, political and environmental aspects, has affected the human life in recent decades. Introducing the sustainable development as the main theme of the third millennium is the result of urban impact on the biosphere and the range of different aspects of human life too. Concentration on differences in dimensions and indicators of sustainable development in one place and having them compared to other places can use fal for planners to realize the development potential and weaknesses. In theme lines, Boroujerd city have been studied as one of the median cities in the West of Iran to assess the indicators of sustainable development. The purpose of this study is to assess indicators of sustainable urban development in Boroujerd town, compared with Iran urban centers. In this study, methodology, is cognitive in terms of objective, and is comparative- analytical in term of identity and the data collection method is documental studies. To assess the level of development, the concept of sustainable development was classified in four dimensions: social, economical, environmental, physical-institutional and 44 indicators were identified. The data were collected in the Boroujerd city and Iran urban centers. Data were analyzed with sign test in SPSS software. The result has shown that there is no difference between Boroujerd city and Iran urban centers in terms of social and physical-institutional indicators. But, economic and environmental indicators have significant differences. The economic condition is not good but the environmental condition is better. On the other hand, taking into account all indices, the sustainability of Borujerd city, almost is same with Iran situation sustainable.